The Effect of Training and Competence on the Quality of Service at the Islamic Hospital in Jakarta, Pondok Kopi - David Muhamad Khadafi; Enjang Sudarman; Sukiman Sukiman (Dinasti Publisher, 2026)
This study aims to determine and analyze in depth the influence of training on service quality, the influence of competence on service quality, and the simultaneous influence of training and competence on service quality at the Jakarta Islamic Hospital Pondok Kopi. This study uses a quantitative approach, namely an approach that emphasizes the collection and processing of data in the form of numbers so that the results of the analysis can be interpreted objectively and measurably. However, this study is also supplemented by qualitative data as support, such as verbal statements in questionnaires, open comments, and the results of consultations or short interviews between researchers and informants to enrich understanding of the variables studied. The study population amounted to 245 employees, while the sample used was 89 respondents selected based on sampling techniques appropriate to the research needs. Hypothesis testing was conducted using the SPSS version 29 analysis tool, which is able to test the relationship between variables simultaneously and accurately. The results show that training (X1) and competence (X2) have a positive and significant influence on service quality (Y) partially. Furthermore, the R-Square test result of 0.402 indicates that 40.2% of the variation in employee performance can be explained by these two variables, while the remaining 59.8% is influenced by factors outside this study. This finding emphasizes the importance of improving training and competency for service quality